2016
DOI: 10.4236/ijg.2016.76062
|View full text |Cite
|
Sign up to set email alerts
|

Ground Magnetic, GPR, and Dipole-Dipole Resistivity for Landfill Investigation

Abstract: Ground magnetic, ground penetrating radar (GPR), and dipole-dipole resistivity were carried out to environmentally investigate a landfill. In this context, these geophysical techniques were conducted to identify the subsurface contents of the landfill, furthermore, specify any possible leakage and/or contamination in the study area. The ground-magnetic survey carried out in the study area comprised 31 profiles each 120 m in length. Different wavelength filters were applied to the measured data. Vertical deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…In addition, Yochim et al (2013) demonstrated the superiority of borehole GPR technology to estimate the water content in a landfill. Khalil and Hassan (2016) also used the GPR technology to identify landfills and assess leakage and pollution. Furthermore, Kondracka et al (2021) compared the advantages and disadvantages of four geophysical methods in landfill characterisation and found that GPR easily detects buried metallic and non-metallic pipelines and building foundations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Yochim et al (2013) demonstrated the superiority of borehole GPR technology to estimate the water content in a landfill. Khalil and Hassan (2016) also used the GPR technology to identify landfills and assess leakage and pollution. Furthermore, Kondracka et al (2021) compared the advantages and disadvantages of four geophysical methods in landfill characterisation and found that GPR easily detects buried metallic and non-metallic pipelines and building foundations.…”
Section: Introductionmentioning
confidence: 99%